Modulation of the mutagenic effect of benzo[a]pyrene and bleomycin by isoflavone extracts in a rat hepatoma cell line - Mendes, Josiane; Tsuboy, Marcela Stefanini Ferreira; Marcarini, Juliana Cristina; Hoffman-Campo, Clara Beatriz; Ribeiro, Lucia Regina [UNESP]; Mantovani, Mário Sérgio (Universidade Estadual de Londrina, 2012)
Epidemiologic studies show that the intake of foods rich in isoflavones (phytoestrogens), such as soybeans, confers protection against various types of cancer, what increases the scientific and popular interest on these compounds. In the present study, phytoestrogens extracts from soybeans were tested for genotoxic potential and modulatory effects on benzo[a]pyrene and bleomycin. Two phytoestrogens were evaluated in vitro, phytoestrogen “A” was supplied by EMBRAPA-Soja, Londrina – PR, and phytoestrogen “B” was purchased in a local drug store. The methods used were the comet assay (genotoxicity and antigenotoxicity) and micronucleus test with cytokinesis block (mutagenicity) in rat hepatoma cells (HTC cell). The isoflavones were tested at three concentrations pre-established by the MTT cytotoxicity assay. Both isoflavone extracts showed no genotoxic effects in the comet assay, but showed induction of micronucleus. In the evaluation of the phytoestrogens for a modulatory effect, both phytoestrogens extracts showed antigenotoxicity in the comet assay.

Estudos epidemiológicos mostram que a ingestão de alimentos ricos em isoflavonas (fitoestrógenos), como a soja, confere proteção contra vários tipos de câncer, o que aumenta o interesse científico e popular sobre esses compostos. No presente estudo, os fitoestrógenos de extrato de soja foram testados quanto aos efeitos genotóxicos e modulador de benzo [a] pireno e bleomicina. Dois fitoestrogênios foram avaliados in vitro, o fitoestrógenos “A” foi fornecido pela Embrapa-Soja, Londrina - PR, e o fitoestrógenos “B” foi comprado em uma farmácia de manipulação local. Os métodos utilizados foram o teste do Cometa (genotoxicidade e antigenotoxicidade) e teste do Micronúcleo com Bloqueio Citocinese (mutagenicidade) em células de hepatoma de rato (HTC celulares). As isoflavonas foram testadas em três concentrações pré-estabelecidas pelo ensaio de citotoxidade MTT. Ambos os extratos de isoflavonas não mostraram efeitos genotóxicos no ensaio do cometa, mas mostraram indução de micronúcleo. Na avaliação dos fitoestrogênios para um efeito modulador, ambos os extratos fitoestrogênios mostraram efeito antigenotóxico no ensaio do cometa.
Keywords: Soy phytoestrogens; Genotoxicity; Mutagenicity; HTC cells; Fitoestrógenos da soja; Genotoxicidade; Mutagenicidade; Células HTC